Improved ORR Performance of Precious Metal‐Free Fe Single‐Atom Catalysts by Heteroatom Doping - Zhexin Pan; Yiming Zhu; Yihong Liu; Wei‐Hsiang Huang; Yujie Cui; Yang Zhao; Menghao Yang; Hongfei Cheng; Nicolas Alonso‐Vante; Jiwei Ma (Advanced Materials Interfaces, 2025)
Abstract The development of platinum group metal (PGM)‐free catalysts is essential to advance the wide application of fuel cells. Single‐atom Fe─N─C catalysts are one type of promising PGM‐free catalysts that can replace the expensive Pt/C catalyst for the electrocatalytic oxygen reduction reaction. However, Fe─N─C catalysts still suffer from poor stability due to the inevitable Fenton reaction. In this work, a doping strategy is demonstrated to alter the electronic structure around the catalytic sites and significantly improve their catalytic activity. In particular, the phosphorous‐doped Fe─N─C catalyst (P─Fe─N─C) achieves a half‐wave potential of 0.885 V versus RHE in 0.1 m KOH and demonstrates excellent stability, with only a 7 mV decay in the half‐wave potential after 10 000 cyclic voltammetry cycles, superior to that of boron‐doped one (B─Fe─N─C). Density functional theory (DFT) calculations further confirm that heteroatom doping favors the ORR process, highlighting the potential of this catalyst for advanced energy applications.